EKSPLORATIF TINGKAT PRODUKTIVITAS AGEN PEMASAR PT. ASURANSI JIWA BUMI ASIH JAYA DISTRIK DEMANGAN CABANG JATENG - Ahmad Yunadi (JESI (Jurnal Ekonomi Syariah Indonesia), 2012)
ABSTRACT This study entitled "Eksplorative Study of Productivity Level by Marketing Agent of PT. Asuransi Jiwa Bumi Asih Jaya District Demangan Branch Central Java". PT. Asuransi Jiwa Bumi Asih Jaya District Demangan Branch Central Java is a company engaged in life insurance services. This study aims to determine the level of productivity and the factors that support the productivity of marketers such as recruitment/selection, training, job satisfaction and leadership. The results showed that all factors such as recruitment/selection, training, job satisfaction and leadership could support the success of the company with a good level of productivity. This is proved by increased of sales policy in every year. PT. Asuransi Jiwa Bumi Asih Jaya District Demangan Branch Central Java do marketing agent recruitment with the involvement of psychologists to get individual characters such enormous interest to sell, talent, intelligence, broad knowledge and ways of communication to others, never give up, persevere and have the character of leaders . Then held training from PAMO, PAG, PAS and the PUM with materials that support the sale of policies and materials on familiar characters on the leader himself. Job satisfaction also appears to marketers when a close relationship between the leader and marketer, as well as between fellow marketers, besides giving provision which consistent with productivity at work. Leadership done by PT. Asuransi Jiwa Bumi Asih Jaya District Demangan Branch Central Java has been very good where marketers provide an appreciation of his leadership and zeal in work. Advised to the company to keep using the recruitment/selection, training, job satisfaction and leadership that already exists to further improve the productivity of marketing agents. Keyword: Productivity, Marketing, Agent, insurance.